The Mode of Delivery and Length of Stay among Pregnant Women with Heart Disease in Makassar - Tri Saputra, Hasdianto; Nurdin, Azizah; Andi Tihardimanto; Dachlia Sri Sakti; Darussalam; Andi Pratiwi (Universitas Airlangga, 2025)
Background: The cardiovascular system undergoes physiological and pathological changes due to pregnancy. Heart disease is the leading cause of maternal morbidity and mortality during pregnancy. Pregnancy-related complications are common in mothers, approximately 1-4% of cases. In most countries in the world, including Indonesia, the number of cases and prevalence of heart disease complicating pregnancy is low. Objectives: This study focuses on the relationship of heart disease in pregnancy with the mode of delivery and length of stay among pregnant women in Dr. Wahidin Sudirohusodo Hospital 2017-2022. Methods: This cross-sectional study was conducted on 124 pregnant women who were determined through a purposive sampling method and carried out in October 2023 - December 2024 at Dr. Wahidin Sudirohusodo Hospital using secondary data, namely medical records of patients diagnosed with heart disease in pregnancy. Data analysis was performed univariately and bivariately using the chi-square comparative test. Results: Correlation between variables was analyzed using chi-square comparison test and a significant correlation was obtained for heart disease in pregnancy with mode of delivery (p-value; 0.001 <0.05), and length of stay (p-value; 0.000) Conclusion: There is a significant relationship between heart disease in pregnancy with mode of delivery and length of stay in laboring women at Dr. Wahidin Sudirohusodo Hospital Makassar. The severity of heart disease in pregnant women can affect the mode of delivery, so counseling before delivery is very important, it is expected to determine the right choice of delivery to reduce the risk of morbidity, mortality and length of stay in mothers.